Development of Novel Real-Time PCR Assays for Detection and Differentiation of Eleven Medically Important Aspergillus and Candida Species in Clinical Specimens - Schabereiter-Gurtner, Claudia (American Society for Microbiology, 2007)
In the present study, novel real-time PCR assays targeting the fungal ITS2 region were developed for the detection and differentiation of medically important Aspergillus species (Aspergillus fumigatus, Aspergillus flavus, Aspergillus nidulans, Aspergillus niger, and Aspergillus terreus) and Candida species (Candida albicans, Candida dubliniensis, Candida glabrata, Candida krusei, Candida parapsilosis, and Candida tropicalis) using a LightCycler instrument. The combination of a group-specific and a universal primer with five Aspergillus or six Candida species-specific biprobes in one reaction mixture facilitated rapid screening and species differentiation by the characteristic peak melting temperatures of the biprobes. Both assays can be performed either as single assays or simultaneously in the same LightCycler run. The analytical sensitivity using pure cultures and EDTA-anticoagulated blood, cerebrospinal fluid (CSF), and tissue samples spiked with A. fumigatus and C. albicans cell suspensions was shown to be at least 1 CFU per PCR, corresponding to 5 to 10 CFU/ml blood and 10 CFU/200 μl CSF or 0.02 g tissue. To assess the clinical applicability, 26 respiratory samples, 4 tissue samples from the maxillary sinus, and 1 blood sample were retrospectively tested and real-time PCR results were compared with results from culture, histology, or a galactomannan enzyme-linked immunosorbent assay (ELISA). Twenty samples (64.5%) were both culture positive and positive by real-time PCR. Six samples (19.4%) showed no growth of fungi but were positive by real-time PCR. However, all of the tissue samples were positive by both PCR and histology. The blood sample showed no growth of Aspergillus, but aspergillosis was confirmed by positive galactomannan ELISA, histology, and PCR results. The remaining samples (16.1%) were culture and PCR negative; also, no other signs indicating fungal infection were observed. Our data suggest that the Aspergillus and Candida assays may be appropriate for use in clinical laboratories as simple and rapid screening tests for the most frequently encountered Aspergillus and Candida species and might become an important tool in the early diagnosis of fungal infections in the future.